FUNGSI SOSIAL CERITA RAKYAT BATU BUJANG LENGONG DI NAGARI ALAHAN PANJANG KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Efanita, Nofel; Nasution, Bakhtaruddin; Hamidin, Hamidin (Jurnal Bahasa dan Sastra, 2013)
The purpose for describe function social strori people stone bachelor lengong di Nagari Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok hasil researeh in is function social ditemukan faef function social yaitu  (1),Studi theory which be usea in research, (2) nature folklore nature, (3)  function social strory people. Type researeh is researeh qualilative data dianalisis with step measuresDescribe result recording in language writler translate result interesting conclusior and write report.of destination in is function social strory people bachelor lengong foun Nagari Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok, (1)  Function social entertain, (2) Function social educate, (3) Function social begueath, (4) Function social tradition, (5)  Function social  identity.